Childhood polyarteritis nodosa presenting as central nervous system vasculitis - Sham Santhanam; Ravikumar Thambithurai; Nataraj Palaniappan; Mukul Vij; Srinivasan Kalyanasundaram (Indian Journal of Rheumatology)
Childhood polyarteritis nodosa (c-PAN) is one of the rare causes of childhood central nervous system (CNS) vasculitis. Nervous system involvement is less common, with peripheral nervous system frequently involved than the CNS. To the best of our knowledge, a very few cases of c-PAN presenting as CNS vasculitis involving both the anterior and posterior circulation have been reported in the literature. Hence, we report a 14-year-old female presenting with extensive CNS vasculitis with severe neurological deficits. She also had systemic symptoms, myalgia, leg ulcers, weight loss, axonal neuropathy, and proteinuria. She was treated with pulse methylprednisolone, monthly intravenous pulse cyclophosphamide, and intravenous immunoglobulin. At the end of 3 months, her proteinuria came down significantly with no major improvement in her neurological status. Hence, c-PAN has to be considered in the differential diagnosis of childhood CNS vasculitis and if not picked up early can lead to severe neurological deficits.